2020
DOI: 10.1093/mnras/staa736
|View full text |Cite
|
Sign up to set email alerts
|

Properties of gamma-ray decay lines in 3D core-collapse supernova models, with application to SN 1987A and Cas A

Abstract: Comparison of theoretical line profiles to observations provides important tests for supernova explosion models. We study the shapes of radioactive decay lines predicted by current 3D core-collapse explosion simulations, and compare these to observations of SN 1987A and Cas A. Both the widths and shifts of decay lines vary by several thousand kilometers per second depending on viewing angle. The line profiles can be complex with multiple peaks. By combining observational constraints from 56 Co decay lines, 44 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 92 publications
(148 reference statements)
2
18
1
Order By: Relevance
“…The original model M15-7b-3 shows a good overall agreement with the observed light curve even though the dome of the calculated light curve should be slightly shifted as a whole to earlier times. The latter effect is easily realized by decreasing the mass of the ejected envelope (Utrobin 2005), which is in perfect agreement with the analysis of Xray and gamma-ray observations, and Fe IR line properties of SN 1987A by Jerkstrand et al (2020). Decreasing the ejecta mass and, as a consequence, the mass of slow-moving hydrogen confined to the inner layers (Table 4) shifts both the rising part of the dome-like maximum of the light curve and the branch declining from the maximum to the radioactive tail to earlier times.…”
Section: Comparison With Observationssupporting
confidence: 90%
See 2 more Smart Citations
“…The original model M15-7b-3 shows a good overall agreement with the observed light curve even though the dome of the calculated light curve should be slightly shifted as a whole to earlier times. The latter effect is easily realized by decreasing the mass of the ejected envelope (Utrobin 2005), which is in perfect agreement with the analysis of Xray and gamma-ray observations, and Fe IR line properties of SN 1987A by Jerkstrand et al (2020). Decreasing the ejecta mass and, as a consequence, the mass of slow-moving hydrogen confined to the inner layers (Table 4) shifts both the rising part of the dome-like maximum of the light curve and the branch declining from the maximum to the radioactive tail to earlier times.…”
Section: Comparison With Observationssupporting
confidence: 90%
“…CONSTRAINING THE PROGENITOR MASS Alp et al (2019) showed that our favorite model M15-7b-3 having an ejecta mass of 19.46 M fits the early X-ray and gamma-ray emission of SN 1987A best compared to other binary-merger explosion models. Jerkstrand et al (2020), in turn, found that a good agreement between 3D models and the gamma-ray decay lines and the UVOIR bolometric light curve of SN 1987A could be achieved with a lower ejecta mass of about 14 M . In the light of these results we computed a set of artificial models M15-7b-3-m2, M15-7b-3-m4, and M15-7b-3-m6 with ejecta masses of 17.46 M , 15.46 M , and 13.46 M , respectively (Table 4).…”
Section: Comparison With Observationsmentioning
confidence: 81%
See 1 more Smart Citation
“…Grefenstette et al (2017) studied Ti emission in Cas A and found that the bulk Ti emission was tilted 58 • into the plane of the sky away from the observer, implying that the NS is moving 58 • out of the plane of the sky toward the observer. This finding is supported by three-dimensional simulations of a Type IIb progenitor by Wongwathanarat et al (2017) and Jerkstrand et al (2020), which suggested that the NS is moving out of the plane of the sky with an angle of ∼30 • .…”
Section: Neutron Star Kick Directionmentioning
confidence: 58%
“…Current 3D SN explosion simulations (e.g. Wongwathanarat, Janka & Müller 2013; Wongwathanarat, Müller & Janka 2015) predict asymmetries in line profiles with line centroid shifts up to about ±500 km s −1 for the IIP case (Jerkstrand et al 2020). For stripped envelope SNe, the scales of these shifts are likely yet larger due to overall higher velocities.…”
Section: Blue-shifted Linesmentioning
confidence: 96%